Parametric studies on corn straw combustion characteristics in a fixed bed: Ash and moisture content. (1st September 2018) - Meng, Xiaoxiao; Sun, Rui; Ismail, Tamer M.; Zhou, Wei; Ren, Xiaohan; Zhang, Ruihan
Abstract: This experiment was conducted on fixed bed combustion in a one-dimensional bench. The effects of ash and moisture content on the combustion characteristics of corn straw were determined. The two parameters directly relate to the burning rate and affect combustion efficiency and the release of gas. The bed temperature distribution, mass loss rate and gas composition were measured in the bed. The results show that the optimum char combustion efficiency was achieved at 10% moisture content of corn combustion. A slight increasing the moisture content to 10% can obtain a higher bed temperature and accelerate the ignition rate in the char oxidation stage, while there is also a slight decrease in the conversion ratio of C to CO. The conversion rate of S to SO2 for 10% moisture content was higher with the temperature zone above 1000 °C. With the increased ash content, there was a slight increase in the average ignition rate; the bottom bed temperature increased with a serious ash slagging. C was converted to CO and presented a slightly increasing trend for higher ash content and the conversion of N to HCN. This work provides an overall understanding of corn combustion for large boiler system. Highlights: Studying the effect of ash and moisture content of corn in fixed bed combustor. With the increase of the moisture content, burning rate decreases. The conversion ratio of N/NO in corn is inverse to moisture content. With the increase of the ash content, the burning rate of the material is slow. The conversion of N to NO at a low speed rate by increasing ash content.